Degree of connectedness among herds of three pig breeds in Korea - LOPEZ, B M; KANG, H S; VITERBO, V S; SONG, C W; SEO, K S (The Indian Journal of Animal Sciences, 2018)
The accuracy of comparing estimated breeding values (EBVs) among animals from different herds depends on the degree of connectedness among herds. In this study, the connectedness rating (CR) method was used to measure the degree of connectedness among pig herds in Korea. Data describing average daily gain (ADG) of three pig breeds (Duroc, Landrace and Yorkshire) from 2000 to 2015 of different herds were used. The results showed that most herds for each breed were well connected to one or a few other herds. All herds in all breeds had an average CR greater than zero. Generally, pig herds in Korea showed low-to-moderate average CR values (1.78-30.85%) with other herds. Among breeds, Duroc had the highest average CR, ranging from 9.79 to 31.07%. The average CR of Landrace ranged from 2.67 to 7.17%, while this value ranged from 1.78 to 28.15% for Yorkshire. Based on these results, national across-herd genetic evaluation in Korea is feasible. However, efforts are still needed to improve and establish the connectedness of few farms for which there was a low CR with other herds to enable more accurate EBV comparison. Furthermore, consistent sharing of boars should be maintained to sustain strong connections among herds.